Performance budgeting in Korea Overview and assessment - Park, Nowook (OECD Publishing, 2015)
This paper tries to shed light on the Korean performance budgeting (PB) system by analysing its strength and limitations by utilising the framework of the OECD 2011 PB survey. It provides an overview of the Korean PB system and describes the Korean system based on the OECD survey results. Lastly, current issues of the Korean PB system are discussed including its future directions. JEL classification: H61, H830 Keywords: Performance budgeting, performance information, budgeting, Korea
Keywords: Finance and Investment; Governance